Yield of bean genotypes with different sowing, irrigation-drought methods in Aguascalientes - Osuna-Ceja, Esteban Salvador; Reyes-Muro, Luis; Padilla-Ramírez José Saúl; Rosales-Serna, Rigoberto; Martínez- Gamiño Miguel A.; Acosta-Gallegos, Jorge A.; Figueroa-Sandoval Benjamín (Revista Mexicana de Ciencias Agrícolas, 2018)
In Mexico, beans (Phaseolus vulgaris L.) are grown mainly in poor rainfed environments, where drought cause low grain yields. We evaluated grain yield of ten bean genotypes under three planting methods and number of plants per hectare: a) furrow at 0.76 m in a single row (90 000 pl ha-1); b) beds in 1.52 m with three rows (145 000 pl ha-1) and; c) beds of 1.52 m with six rows (260 000 pl ha-1) and two humidity conditions: Rainfed (T) and Rainfed plus two supplementary irrigations (T+RS) applied in the reproductive phase. The materials used were: type Pinto (Centauro, Libertad, Centenario, Saltillo, Bravo and Coloso); Flor de Mayo (Guanajuato, Dolores and Eugenia) and; Azufrado. The experiment was located in Pavilion and Sandovales, Aguascalientes; sowing was on July 31th and August 1th , 2012. The drought susceptibility index (ISS) was estimated between both humidity conditions. Sowing methods significantly (p< 0.01) affected the yield in both humidity conditions, being the highest with six rows, followed by the one with three rows and finally the single row, with yields of 2.94, 2.18 and 1.72 t ha-1 for T + RS and 1.14, 0.93 and 0.71 t ha-1 for T, respectively. The response of the genotypes was significant (p< 0.01), outstanding Pinto Centauro and Libertad (2.70 and 2.65 t ha-1) with T+RS and Pinto Saltillo (1.06 t ha-1) in T, respectively. Based on the yield reduction and ISS, all genotypes were moderately drought tolerant.